2009
DOI: 10.1371/journal.pone.0004469
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Status at Birth: Its Relation to Newborn Physical Parameters at Birth and Gestational Age

Abstract: BackgroundRefractive status at birth is related to gestational age. Preterm babies have myopia which decreases as gestational age increases and term babies are known to be hypermetropic. This study looked at the correlation of refractive status with birth weight in term and preterm babies, and with physical indicators of intra-uterine growth such as the head circumference and length of the baby at birth.MethodsAll babies delivered at St. Stephens Hospital and admitted in the nursery were eligible for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
1
37
1
Order By: Relevance
“…Weale (2002) described the pattern as being ‘u’-shaped. Prevalence is high in the first few weeks of postnatal life (Zonis and Miller, 1974; Fulton et al, 1980; Varghese et al, 2009), but then decreases in early childhood (e.g. Atkinson et al, 1996), only to increase again in the teenage years as myopia emerges (e.g., Parssinen, 1990; Laird, 1991; Lin et al, 1999).…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Weale (2002) described the pattern as being ‘u’-shaped. Prevalence is high in the first few weeks of postnatal life (Zonis and Miller, 1974; Fulton et al, 1980; Varghese et al, 2009), but then decreases in early childhood (e.g. Atkinson et al, 1996), only to increase again in the teenage years as myopia emerges (e.g., Parssinen, 1990; Laird, 1991; Lin et al, 1999).…”
Section: Prevalencementioning
confidence: 99%
“…At or soon after birth, anisometropia prevalence has been reported to be 17.3% (n=300, >1D difference between vertical or horizontal meridia, Zonis and Miller, 1974) to 30% (n= 256, >1D difference in SE, Varghese et al, 2009). Larger scale, more population-based studies have been conducted on children from the age of 6 months (e.g., Dirani et al, 2010; Borchert et al, 2010) and, if the high anisometropia prevalence figures in the perinatal period generalise to a larger population, prevalence appears to drop considerably by the age of one year.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a relationship between birthweight (BW) and refraction at birth in both term and premature infants has been reported, weight being the better predictor than gestational age (GA) (Varghese et al. ). Furthermore, a study from New Zealand showed an increased risk of strabismus and subnormal visual maturation in moderate prematurity and/or low BW compared with normal BW at 6 years of age (Robaei et al.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is currently emerging that even near-term birth predisposes those children to a higher risk of mortality and morbidity than term infants (Engle et al 2007). To date, very few studies have focused on the ophthalmological aspects of this particular subset of children (Robaei et al 2006;Nilsson et al 2011). Previously, a relationship between birthweight (BW) and refraction at birth in both term and premature infants has been reported, weight being the better predictor than gestational age (GA) (Varghese et al 2009). Furthermore, a study from New Zealand showed an increased risk of strabismus and subnormal visual maturation in moderate prematurity and/or low BW compared with normal BW at 6 years of age (Robaei et al 2006).…”
Section: Introductionmentioning
confidence: 99%